An inappropriate sense of place - Mortensen, Torill Elvira (AoIR Selected Papers of Internet Research, 2013)
This is a discussion of how mediacity influences the understanding of communication, based on Joshua Meyrowitz’ work No sense of Place, where his concepts are used on digital communication through a discussion of two examples of inappropriate communication online. This discussion reactivates his understanding of how media changes society, while it underlines the extent to which digital media have changed society. The media reality Joshua Meyrowitz addressed in 1985 no longer exists. Since then print and electronic media have converged in and been altered by digital media, and the sense of place has changed. It is still vital for the understanding of communication to understand how mediacity changes the settings – the very stage on which we perform as everyday actors. This is a theoretical paper where the original concepts of Meyrowitz will be challenged through other understandings of some of his core concepts. The following exemplifies the discussion, which will be expanded on and explored more deeply for the conference presentation.